2010
DOI: 10.1098/rsta.2009.0279
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic coordination clusters and networks: synthesis and topological description

Abstract: With the discovery of the phenomenon of single-molecule magnetism, coordination chemists have turned their attention to synthesizing cluster aggregates of paramagnetic ions. This has led to a plethora of coordination clusters with various topologies and diverse magnetic properties. In this paper, we present ways of describing and understanding such compounds as well as outlining a new approach, which we have recently developed, to describing cluster topology. Our approach is based upon and pays tribute to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 36 publications
0
57
0
Order By: Relevance
“…The curves for 6 and {5 + 6} show a steepening of the decrease in χT below about 8 K, which was interpreted as the effect of antiferromagnetic Dy III -Dy III interactions superimposed on the thermal depopulation of Dy III MJ sub-levels. 29 The curve for Fe4Dy2 (7), by contrast shows a significant upturn below 10 K, which is significantly larger than those seen for the Er III analogues. Such an upturn indicates that the Fe III -Dy III interactions in 7 have forced the two Dy III spins into a coparallel ferromagnetic arrangement.…”
Section: Synthesis Of [mentioning
confidence: 92%
See 1 more Smart Citation
“…The curves for 6 and {5 + 6} show a steepening of the decrease in χT below about 8 K, which was interpreted as the effect of antiferromagnetic Dy III -Dy III interactions superimposed on the thermal depopulation of Dy III MJ sub-levels. 29 The curve for Fe4Dy2 (7), by contrast shows a significant upturn below 10 K, which is significantly larger than those seen for the Er III analogues. Such an upturn indicates that the Fe III -Dy III interactions in 7 have forced the two Dy III spins into a coparallel ferromagnetic arrangement.…”
Section: Synthesis Of [mentioning
confidence: 92%
“…[2][3][4] Therefore, the synthesis and characterization of high-nuclearity 3d-4f SMMs have attracted intensive attention in recent years. [5][6][7][8][9] Although many studies on 4f-4f or 3d-3d interactions have been reported, [10][11][12][13][14][15][16][17] research on 3d-4f exchange interactions is less developed. [18][19][20][21][22][23][24] Furthermore, according to the model of free-ion electron densities for all Ln III ions, the shape of the 4f electron density for the Dy III ion is oblate, while that for Er III is prolate.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of Bioinorganic Chemistry there is a continuous search for various nuclearity oxidebridged complexes to model M x sites in biomolecules, including understanding the assembly of the multinuclear Fe III /O 2-core of the iron-storage protein ferritin [21,22] and elucidating the structure, spectroscopic properties and mechanistic aspects of the {CaMn 4 O 5 } core of the H 2 O oxidizing complex within the photosynthetic apparatus of green plants and cyanobacteria [23 -27]. The latter opened up a new era in Mn chemistry and led to the realisation that manganese can be stabilized in the formal oxidation state III by certain ligands, even in the presences of II and IV states.…”
Section: Edited Feb 6mentioning
confidence: 99%
“…Several reviews have already been published on SMMs which highlight strategies towards their synthesis and optimisation as well as understanding the factors determining the relaxation dynamics in such molecules [1,[3][4][5][6][7][8][9]. However, it is still a challenge to understand the structure-property relationships.…”
Section: Introductionmentioning
confidence: 99%